Reconstruction with a Custom made Prosthetic Wrist Arthrodesis after Bone Tumor Resections of the Distal Radius. Single Centre Experience - Szostakowski, Bartlomiej; Staals, Eric; Onwordi, Lyris; Pollock, Robin; Skinner, John A. (Revista Brasileira de Ortopedia, 2021)
Objective The present study aimed at analyzing the clinical, radiological and functional results of the reconstruction of the distal radius after tumor resection with a custom-made metal arthrodesis implant and compare them with other types of distal radius reconstruction, as presented in the literature.To our best knowledge, this is the first article describing this particular type of implant and patient functionality.Methods Functional outcomes of reconstruction of the distal radius were assessed in a series of 4 patients. Three of the patients having had resection of giant cell tumors (GCTs), one patient having had resection of osteosarcoma.Results There were no major implant-related complications like infection, nonunion or loosening. Two patients had to undergo further surgery for protruding metalwork. Overall function was good according to the Musculoskeletal Tumor Society MSTS and Disabilities of the Arm, Shoulder, and Hand (DASH) scores.Conclusion The present study shows that custom-made metal arthrodesis implant benefits from the fact that it can be used as a salvage option when other treatments have failed, or it can be used as a primary option in cases in which there is limited bone stock after distal radius tumor resection.
Keywords: sarcoma; giant cell tumors; distal radius; wrist; arthrodesis; prosthesis